Identification and citizenship in Africa : biometrics, the documentary state and bureaucratic writings of the self - Awenengo Dalberto, Séverine; Banegas, Richard (Routledge contemporary Africa Series, 2021)
In the context of a global biometric turn, this book investigates processes of legal identification in Africa ‘from below,’ asking what this means for the relationship between citizens and the state. Almost half of the population of the African continent is thought to lack a legal identity, and many states see biometric technology as a reliable and efficient solution to the problem. However, this book shows that biometrics, far from securing identities and avoiding fraud or political distrust, can even participate in reinforcing exclusion and polarizing debates on citizenship and national belonging. It highlights the social and political embedding of legal identities and the resilience of the documentary state. Drawing on empirical research conducted across 14 countries, the book documents the processes, practices, and meanings of legal identification in Africa from the 1950s right up to the biometric boom. Beyond the classic opposition between surveillance and recognition, it demonstrates how analysing the social uses of IDs and tools of identification can give a fresh account of the state at work, the practices of citizenship, and the role of bureaucracy in the writing of the self in African societies. This book will be of an important reference for students and scholars of African studies, politics, human security, and anthropology and the sociology of the state. -- Présentation de l'éditeur.